Sex and age differences in cardiovascular risk factors and lifestyle in patients recently diagnosed with diabetes mellitus: A cross-sectional study in Spanish primary health care - Pilar Vich-Pérez; Belén Taulero-Escalera; Victoria García-Espinosa; Laura Villanova-Cuadra; Paula Regueiro-Toribio; Ignacio Sevilla-Machuca; Julia Timoner-Aguilera; Mario Martínez-Grandmontagne; Tania Abós-Pueyo; Cristina Álvarez-Hernandez-Cañizares; Germán Reviriego-Jaén; Alberto Serrano-López-Hazas; et al. (PLoS ONE, 2025)
Aims To describe the main characteristics of patients recently diagnosed with DM regarding cardiovascular risk factors and diabetes-related complications, compare possible differences according to sex and age group, and examine healthy lifestyle behaviors such as adherence to the Mediterranean diet and physical activity and their associated factors. Methods A cross-sectional, multicenter, observational study of 681 patients aged >30 years diagnosed with diabetes mellitus in the previous 4 years was performed. The patients were treated in primary care centers in Madrid (Spain). The variables were obtained from their electronic medical records, physical examination, complete analysis, and lifestyle questionnaires. Results The main comorbidities were: hypercholesterolemia (64.4%; 95% CI, 60.6–68.2), hypertension (55.2%; 95% CI, 51.3–59.1), obesity (58.9%; 95% CI, 55.2–62.6), metabolic syndrome (58.5%; 95% CI, 54.6–62.5); and hypertriglyceridemia (25.3%; 95% CI, 21.9–28.7). Despite being newly diagnosed, 7.6% (95% CI, 5.4–9.8) had microalbuminuria, and 10.3% (95% CI, 8.0–12.6) cardiovascular disease. The main unhealthy lifestyles were: low physical activity (52%; 95% CI, 48.1–55.9), alcohol consumption (47.7%; 95% CI, 44.0–51.5) and smoking (19.2%; 95% CI, 16.2–22.3). Compared with men, women had more morbid obesity (9.7% vs 4.6%, p = .014), worse lipid profile (total cholesterol: 184 (IQR, 158–207) vs. 165 (IQR, 144–192), p < .01), less treatment with metformin (74.8% vs. 84.4%, p < .01) and antiplatelet agents (8.1% vs.18.6%, p < .01), but women had fewer comorbidities. Patients with a high educational level (OR = 1.90, 95% CI, 1.28–2.81)) and those >60 years (OR = 1.49; 95% CI, 1.01–2.21) were more adherent to the Mediterranean diet, and the older ones did less intense exercise (OR = 0.34, 95% CI, 0.16–0.75). Normal blood pressure was associated with Mediterranean diet (OR = 1.52; 95% CI, 1.05–2.21) and high physical activity (OR = 4.03; 95% CI, 1.69–9.61); and body mass index was inversely associated with physical activity (OR = 0.92; 95% CI, 0.85–0.99). Conclusions Patients newly diagnosed with diabetes mellitus may also have crucial cardiovascular risk factors and comorbidities at the onset of the disease. However, patients with a healthy lifestyle were more likely to have a normal blood pressure and a lower body mass index.